Pengaruh Penambahan Fruktosa Pada Media Potato Dextrose Agar (PDA) Terhadap Pertumbuhan Jamur Candida Albicans - Anas Fadli Wijaya; Rian Anggia Destiawan (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2020)
Candida is a fungal infection caused by one of the Candida species, the most common being Candida albicans. Diagnosis of candidiasis due to C. albicans can be done in various ways, but the gold standard for examination is by culture. Specimen culture is carried out by planting on mushroom media. Potato Dextrose Agar (PDA) media is the most commonly used medium for culturing C. albicans. The amount of nutrient content in the media affects the level of fertility and incubation time of the microbes grown on the media. In PDA media, the type of sugar (dextrose) used for nutrition is monosaccharide. There are many types of monosaccharides, one of which is fructose. The purpose of this study was to determine the effect of adding fructose to PDA media on the growth of C. albicans. This study was a laboratory experimental study using the post test control group design only method using 16 replications and 2 treatments, namely PDA media without the addition of fructose and PDA media with the addition of fructose. The results showed that the average number of C. albicans growth on PDA media without the addition of fructose was 376.56 colonies while on PDA media with the addition of fructose it was 289.19 colonies. The value of p = 0.000 with a 2-way significance level (α = 0.05) then p <α. So there is a significant difference between the number of C. albicans fungal colonies on PDA media with and without the addition of fructose. The addition of fructose causes the growth of C. albicans to be slower than without the addition of fructose.